Kombinasi Aplikasi Canva Dan Pixlr Dalam Memaksimalkan Konten di Media Sosial: (Pelatihan pada Pelaku UMKM di wilayah Kelurahan Ngaliyan) - Alfin Muslikhun; Rowiyani Rowiyani; Mukhlidin Mukhlidin; Khansa Aulia Anissa'adah (Jurnal Pelayanan Masyarakat, 2024)
Canva and PIXLR are applications that can be operated through computers and smartphones. Many people have not been able to maximize the potential of this application to become a support in creating content in entrepreneurship. MSME players in the Ngaliyan Kendal urban village area, on average, have not used a combination of Canva and PIXLR applications in creating content to promote their products on social media and marketplaces. The Canva application in maximum use must be paid (pro) so that by combining the combination with the PIXLR application can get maximum results without having to pay (pro). This community service activity aims to provide knowledge to MSME players in the Ngaliyan village area on how to maximize the Canva application with PIXLR to produce good content without having to pay (pro). This community service activity is expected to be able to improve the skills of MSME players so that they can create the right content so that they can minimize costs and improve the performance of both themselves and their businesses. The results of this activity are that MSME players install and operate the Canva and PIXLR applications for every content creation. MSME players feel very helped because without having to subscribe to pay (pro) it turns out that they can get results almost equivalent to subscribing (pro).